2005
DOI: 10.1038/ng1676
|View full text |Cite
|
Sign up to set email alerts
|

Genomic buffering mitigates the effects of deleterious mutations in bacteria

Abstract: The relationship between the number of randomly accumulated mutations in a genome and fitness is a key parameter in evolutionary biology. Mutations may interact such that their combined effect on fitness is additive (no epistasis), reinforced (synergistic epistasis) or mitigated (antagonistic epistasis). We measured the decrease in fitness caused by increasing mutation number in the bacterium Salmonella typhimurium using a regulated, error-prone DNA polymerase (polymerase IV, DinB). As mutations accumulated, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 28 publications
8
141
2
Order By: Relevance
“…Thus, to dissect the genetic basis of inbreeding depression, it is essential to separate observed molecular responses to inbreeding into causal effects and secondary consequences. Moreover, genetic buffer mechanisms that counterbalance genetic defects at optimal conditions are thought to be less effective under stressful conditions, which can result in expression of cryptic genetic variation (Rutherford and Lindquist, 1998;Maisnier-Patin et al, 2005;Bobula et al, 2006). Expression of this cryptic deleterious genetic variation can partly explain the observation that inbreeding depression is often more severe under specific and more stressful environmental conditions (Armbruster and Reed, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to dissect the genetic basis of inbreeding depression, it is essential to separate observed molecular responses to inbreeding into causal effects and secondary consequences. Moreover, genetic buffer mechanisms that counterbalance genetic defects at optimal conditions are thought to be less effective under stressful conditions, which can result in expression of cryptic genetic variation (Rutherford and Lindquist, 1998;Maisnier-Patin et al, 2005;Bobula et al, 2006). Expression of this cryptic deleterious genetic variation can partly explain the observation that inbreeding depression is often more severe under specific and more stressful environmental conditions (Armbruster and Reed, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent experiments confirmed that bacteria carrying multiple mutations grow better when the chaperones GroEL or DnaK are overexpressed (Fares et al 2002;MaisnierPatin et al 2005). But, although it was shown that the mutations were present in the bacterial genomes and that the levels of chaperones were enhanced, there is no evidence that the mutations caused a massive misfolding and that this led to upregulation of the chaperones' expression (Moran 1996;Maisnier-Patin et al 2005). Moreover, it is known that overexpression of the chaperones facilitates folding of many native proteins, not only the mutated ones (Genevaux et al 2004;1 These authors contributed equally to this work.…”
mentioning
confidence: 99%
“…In the bacterium Salmonella typhimurium, a decreased level of fitness was observed when mutations were accumulated (Maisnier-Patin et al, 2005). Intriguingly, levels of the heat-shock proteins DnaK and GroEL were increased in lineages harboring many mutations, and the overexpression of GroEL further increased the fitness of lineages (Maisnier-Patin et al, 2005). The overexpression of GroEL in Escherichia coli attenuated the growth retardation caused by harmful mutations as well (Fares et al, 2002).…”
Section: Antiapoptotic Function Of Molecular Chaperones In Tumor Cellsmentioning
confidence: 96%
“…Blagosklonny et al (1996) reported that p53 mutant (p53V143A) failed to obtain or stabilize correct conformation without functional Hsp90, suggesting that molecular chaperones can make mutant proteins survive in cancer cells. In the bacterium Salmonella typhimurium, a decreased level of fitness was observed when mutations were accumulated (Maisnier-Patin et al, 2005). Intriguingly, levels of the heat-shock proteins DnaK and GroEL were increased in lineages harboring many mutations, and the overexpression of GroEL further increased the fitness of lineages (Maisnier-Patin et al, 2005).…”
Section: Antiapoptotic Function Of Molecular Chaperones In Tumor Cellsmentioning
confidence: 99%